In vitro control of Fusarium solani and F. oxysporum the causative agent of brinjal wilt (Dhaka University Journal of Biological Sciences, 2014)
Seven soil fungi viz. Aspergillus flavus, A. fumigatus, A. niger, A. terreus, Penicillium sp., Trichoderma harzianum and T. viride associated with the rhizosphere, non?rhizosphere and rhizoplane of brinjal plants were selected to observe their antagonistic potential against the test fungi Fusarium oxysporum and F. solani . Out of seven soil fungi T. harzianum was found most effective to control the growth of both the test fungi. Plant parts extract of Allium sativum, Asparagus racemosus, Azadirachta indica, Cassia alata, Ocimum sanctum, Zingiber officinale and Datura metel were evaluated for their in vitro efficacy at 5, 10 and 20% concentration against the test fungi. Datura metel, and C. alata and A. indica was found most efficient inhibitor of F. solani and F. oxysporum, respectively. Five fungicides viz., agridazim 50 wp, cozeb 80 wp, newban 50 wp, sunvit 50 wp and vitavax 200 B were evaluated for their in vitro efficacy at 500 ppm concentration against F. solani and F. oxysporum. Vitavax 200B was found most efficient inhibitor of both the test fungi. DOI: http://dx.doi.org/10.3329/dujbs.v23i1.19826 Dhaka Univ. J. Biol. Sci. 23(1): 53-60, 2014